2014
DOI: 10.1093/ejcts/ezu496
|View full text |Cite
|
Sign up to set email alerts
|

Transoesophageal spinal cord stimulation for motor-evoked potentials monitoring: feasibility, safety and stability

Abstract: Transoesophageal stimulation for MEPs monitoring was feasible without difficulty and safe. Although its stability to anaesthetic agents was similar to that of transcranial stimulation, its technical ease and small interindividual variability warrants further studies on the response to spinal cord ischaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…7,8 We have previously reported that transesophageal (TE) electrical stimulation of the spinal cord can safely and easily elicit myogenic MEPs by conventional equipment for TC-MEP. 9 We found that stimulation intensity was always supra-maximal for TE-MEP, which may be desirable to avoid amplitude fading of myogenic potentials, and interindividual variability is small. This made us hypothesize that specificity and accuracy to spinal cord ischemia may be improved by TE stimulation if its response is at least as quick and sensitive as that of TC-MEP.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…7,8 We have previously reported that transesophageal (TE) electrical stimulation of the spinal cord can safely and easily elicit myogenic MEPs by conventional equipment for TC-MEP. 9 We found that stimulation intensity was always supra-maximal for TE-MEP, which may be desirable to avoid amplitude fading of myogenic potentials, and interindividual variability is small. This made us hypothesize that specificity and accuracy to spinal cord ischemia may be improved by TE stimulation if its response is at least as quick and sensitive as that of TC-MEP.…”
mentioning
confidence: 76%
“…We have previously reported that TE stimulation can be performed by supra-maximal intensity, whereas TC stimulation intensity is usually supra-threshold. 9 This is due to the safety issue of brain electrical stimulation and difficulty in correctly positioning TC stimulation electrodes. It is known that response of alpha motor neurons to excitatory post-synaptic potentials is nonlinear, and an input exceeding a firing threshold produces a full response and anything below it produces no response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anesthesia and instrumentation procedures were performed according to previously reported methods. 14 , 15 Briefly, the animals were anesthetized with intravenous infusion of propofol (12-24 mg/kg/h) and remifentanil (12-24 μg/kg/h) and were maintained on mechanical ventilation. For MEP recording, a Neuropak MEB-2200 system (Nihon Kohden, Tokyo, Japan) was used for data acquisition, processing, and analysis, with SEN-4100 equipment for electrical stimulation (Nihon Kohden, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that transesophageal MEP (TE-MEP), which we call monopolar TE-MEP (monoTE-MEP) in this study, is feasible, safe, and superior to TC-MEP in terms of stability, response time to ischemia/reperfusion, and prognostic value in canine experiments. 14 , 15 We think that it is because supramaximal intensity stimulation can be applied safely and easily to the spinal cord. However, cervical cord stimulation results in the direct stimulation of the cervical alpha motor neurons with strenuous forelimb movement, which may be dangerous in clinical settings, and precludes forelimb potentials to be used as a real-time control.…”
mentioning
confidence: 99%